Exhausting and difficult or easy: the association between psychological flexibility and study related burnout and experiences of studying during the pandemic - Asikainen, Henna; Katajavuori, Nina (Frontiers in Education, 2023)
The Covid-19 pandemic caused a decline in students' well-being, but on the other hand, students' experiences of online learning and studying vary widely. The aim of this study is to examine the relationship between psychological flexibility and study-related burnout and to explore whether students with different levels of psychological flexibility have experienced burnout and online studying during Covid-19 differently. The data was collected from first-year life-science students (N = 296) in spring 2021. The relationship between psychological flexibility and study-related burnout was explored with Pearson's correlation and linear regression. Students' open-ended responses about their experiences of online learning were analysed with inductive content analysis and the categories were quantified. Three different groups (high, middle, low) were made based on respondents' psychological flexibility, and the differences in their study-related burnout were analysed with ANOVA and Tukey's test, and differences in online learning experiences were analysed with a Chi-square test. The results showed that there was a negative relationship between psychological flexibility and study-related burnout. In addition, experiences of study-related burnout and online studying differed statistically significantly between the different groups. The results show that psychological flexibility is an important factor in enhancing students' well-being and learning during the pandemic. This is a provisional file, not the final typeset article even reduced study-related burnout (Parpala et al., 2021). The effects of the pandemic have been different for different students, but we still know little about what factors affect different experiences of studying in the pandemic situation.Several studies have shown that psychological flexibility has a great influence on well-being (Hayes